Tick Rhipicephalus microplus Canestrini: Biological, morphological and biological activity - Braga, Andrina Guimarães Silva; Lima, Renato Abreu; Celestino, Caroline Oliveira; Facundo, Valdir Alves (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2017)
The Brazilian cattle herd is the second largest in the world and the first largest exporter and producer of beef. Nevertheless, the direct losses due to parasitism by Rhipicephalus microplus are due to weight loss, low milk production and decreased quality of leather. Thus, this study consists of a literature review on the Brazilian cattle herd associated with damage caused by pests. databases were used: LILACS, SciELO and PubMed and through keywords such as ectoparasites, ticks and Brazilian cattle became the research. It was found that in recent decades has been given an extreme economic importance for Brazilian agriculture aiming to decrease the biological control of pest attack.